(untitled) (Nóema, 2017)
This paper deals mainly with three issues: how people interact with linguistically codified messages in everyday life? How this affects people’s behaviour? And how does this thing relates to practicing philosophy? These three issues are faced with the help two concepts: “affective reading” regards the first two of them, while “strategic hermeneutics” regards the last one. This paper thus starts with the analysis of the meaning of affective reading and tries to show how this way of reading is practiced on everyday basis to organize our actions. Then the focus turns to philosophical applications of the affective reading to show how much it affects our discipline. Strategic hermeneutics takes here its place on the stage. Indeed, this concept is the application of affective reading as a philosophical tool and method. Hence, it’s shown how to use this kind of tool with a theoretical analysis and an example given. At the end of the paper I’ve tried to display how this philosophical method affects the foundation and development of the philosopher’s ego under the prospective of Lacan’s theory of Oedipus’ complex.